Pengembangan Model Pembelajaran Kimia Pangan Berbasis Teori Sosial Kognitif Bandura - Husain, Halimah; Magfirah, Nita; Sudding, Sudding; Ramdani, Ramdani (Program Pasca Sarjana UNM, 2023)
The objective of this research was to develop a model of food chemistry learning process to guide student’s attitude and behaviour on healthy eating pattern and facilitating their academic achievement. The participants were student who enrolled of food chemistry course. Preliminary results identified 90% of students were enjoy the course’s learning process, and 80% of them argued that the course was very valuable. However, there were 40% among participants experienced teacthing troubles to understand the terms of chemistry reactions, particularly during food processing. In addition, their knowledge related to food chemistry was not applied to be guidance in choosing everyday food consumption especially during they were in university.As conclusion from the preliminary result, learning’s model is critically needed in order to (1) enhance the student’s knowledge, particularly in the area of reaction of chemistry compound (nutrition value) during food processing and (2) improve of student’s attitude and behaviour in well-selecting of healthy food. Social cognitive Bandura is selected approach to be incorporated with learning process of food chemistry by the following reasons: (1) modelling enabled, (2) self-efficacy, (3) observational learning, and (4) motivation and reinforcement.